Development of a Venous Collapse Prevention Device for Blood Draw - Liu Jan; Heumann Maximilian; Stewart Kent W.; Pott Peter P. (Current Directions in Biomedical Engineering, 2022)
Blood sampling typically involves puncturing a superficial vein with a needle and then creating a vacuum (e. g., with a syringe) to transfer the blood from the venous system to the collection container. In some cases, the venous walls collapse due to excessive vacuum generated. In this work, a device is presented that prevents venous collapse and can be combined with any blood collection system available on the market. The mechanism of preventing venous collapse is based on a tubular segment interconnected between the needle and the syringe, which collapses at a lower vacuum pressure than the vein. The prototype was tested and evaluated using a test rig that simulates venous blood draw. The experiments proved the functionality of the device on a vein phantom.